Reduced Degrees of Freedom in Space-Time Adaptive Processing for Space-based Early Warning Radar - Keqing DUAN; Yufan LI; Xingjia YANG; Zizhou QIU; Yongliang WANG (Leida xuebao, 2022)
The clutter of space-based early warning radar exhibits tight coupling in the azimuth-elevation-Doppler domain due to the high speed of satellites and the Earth’s rotation. As a result, conventional Space-Time Adaptive Processing (STAP) suffers significant performance degradation when detecting slow moving targets. The azimuth-elevation-Doppler three-dimensional STAP method provides the ability to decouple clutter and thus can achieve sub-optimal performance for clutter suppression. However, in contrast to the situation in non-sidelooking airborne early warning radar, this method requires large system degrees of freedom when applied to space-based early warning radar. Therefore, in practice, both the computational load and the sample requirement are too large to meet. In this study, the space-time signal model of the planar array for space-based early warning radar is first constructed. Then, the tight coupling characteristic of clutter in the azimuth-elevation-Doppler domain is analyzed in detail. On this basis, a novel three-dimensional STAP method with reduced degrees of freedom with factored structure is proposed. The sidelobe clutter is first suppressed via amplitude taper in azimuth, and the mainlobe clutter responding to each ambiguous range is further canceled by adaptive processing in the elevation-Doppler domain. The simulation results show that the proposed method can achieve sub-optimal performance under low computational load and limited sample conditions. Therefore, the proposed method is suitable for practical application in space-based early warning radar.